Huge Primary Splenic Epithelial Cyst-Case Report - Faridi, Javeria (International Journal of Pathology, 2021)
Splenic cyst are rare. Only few cases have been reported. Mostly are hydatid cyst, epithelial cyst are very rare. Sign and symptoms are usually that of mass in abdomen. This is a case report of splenic epithelial cyst in 14 years old boy who presented with abdominal distension. Cyst with spleen removed and send for histopathology. On microscopy it has confirmed as primary epithelial cyst